The World of gymnastics - Peter Tatlow; Tatlow, Peter, 1922- (New York : Atheneum, 1978)
This is handsome book, written by authorities in the gymnastics world, explains what gymnastics it is all about and presents in words and pictures an up-to-the minute view of the sport and its personalities in all the top gymnastics nations.
Includes index.
Keywords: Gymnastics